PENGARUH KUALITAS PRODUK,KUALITAS PELAYANAN DAN PROMOSI PADA UNICCRAB SEAFOOD MALANG TERHADAP KEPUASAN KONSUMEN (Studi Kasus Pada Konsumen Uniccrab Seafood Soekarno Hatta Malang) - Nur Rochman; M. Hufron; Siti Asiyah (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis research was conducted at Malang Uniccrab Seafood Restaurant in Lowokwaru District, Malang City. This type of research used in this research is quantitative research. The purpose of this study was to determine the effect of product quality, service quality, promotion on customer satisfaction. The variables of product quality, service quality, promotion, while the dependent variable is customer satisfaction. The sample used in this study was 100 respondents who made food purchases at Seafood Uniccrab Malang. Data collection techniques using a questionnaire. The analytical method used is the validity test, reliability test, normality test, classic assumption test, hypothesis test, determination test with the help of SPSS software. The results showed that the variables of product quality, service quality, promotion partially and simultaneously had a positive and significant effect on customer satisfaction. Keywords: customer satisfaction, product quality, service quality, promotion